Targeting JAK/STAT Signaling Antagonizes Resistance to Oncolytic Reovirus Therapy Driven by Prior Infection with HTLV-1 in Models of T-Cell Lymphoma - Shariful Islam; Claudia M. Espitia; Daniel O. Persky; Jennifer S. Carew; Steffan T. Nawrocki (Viruses, 2021)
Human T-cell leukemia virus type 1 (HTLV-1) is a retrovirus that infects at least 10 million people worldwide and is associated with the development of T-cell lymphoma (TCL). The treatment of TCL remains challenging and new treatment options are urgently needed. With the goal of developing a novel therapeutic approach for TCL, we investigated the activity of the clinical formulation of oncolytic reovirus (Reolysin, Pelareorep) in TCL models. Our studies revealed that HTLV-1-negative TCL cells were highly sensitive to Reolysin-induced cell death, but HTLV-1-positive TCL cells were resistant. Consistent with these data, reovirus displayed significant viral accumulation in HTLV-1-negative cells, but failed to efficiently replicate in HTLV-1-positive cells. Transcriptome analyses of HTLV-1-positive vs. negative cells revealed a significant increase in genes associated with retroviral infection including interleukin-13 and signal transducer and activator of transcription 5 (STAT5). To investigate the relationship between HTLV-1 status and sensitivity to Reolysin, we infected HTLV-1-negative cells with HTLV-1. The presence of HTLV-1 resulted in significantly decreased sensitivity to Reolysin. Treatment with the JAK inhibitor ruxolitinib suppressed STAT5 phosphorylation and expression of the key anti-viral response protein MX1 and enhanced the anti-TCL activity of Reolysin in both HTLV-1-positive and negative cells. Our data demonstrate that the inhibition of the JAK/STAT pathway can be used as a novel approach to antagonize the resistance of HTLV-1-positive cells to oncolytic virus therapy.